Determinants of service innovation: a typology of sports federations. (1st January 2013) - Winand, Mathieu; Vos, Steven; Zintz, Thierry; Scheerder, Jeroen
The increasing commercialisation of the sports sector and changing consumer demands are some of the issues that create challenges for non-profit sports in contemporary society. It is important for managers and marketers of these organisations to innovate because innovation is a way to grow within a competitive environment and to meet customers' expectations. The present study aims to develop an explorative typology of sports federations based on their attitudes and perceptions of determinants of innovation and their innovation capacity. A cluster analysis suggested three clusters with different responses towards service innovation: traditional sports federations, financially secure sports federations and competitive sports federations. Sports federations perceiving competition in terms of financial and human resources, favouring change and paid staff involvement in decision-making processes, and with negative economic perceptions are significantly more innovative. These findings have implications for the management and marketing of non-profit sports organisations.